2019
DOI: 10.1016/j.soscij.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

In the name of truth: People’s reactions to ingroup and outgroup members who self-disclose a severe error

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Consistent with this idea, examining so-called moral rebels, Monin et al (2008) showed that their appreciation depends on the psychological closeness and self-relevance of the situation. Furthermore, a correlational study conducted by Rullo et al (2018) confirmed that the judgment of a social target who reveals an uncomfortable truth varies according to the self-relevance of the situation to the respondents.…”
Section: Discussionmentioning
confidence: 84%
“…Consistent with this idea, examining so-called moral rebels, Monin et al (2008) showed that their appreciation depends on the psychological closeness and self-relevance of the situation. Furthermore, a correlational study conducted by Rullo et al (2018) confirmed that the judgment of a social target who reveals an uncomfortable truth varies according to the self-relevance of the situation to the respondents.…”
Section: Discussionmentioning
confidence: 84%
“…For this reason, people are able to behave badly but also to provide moral motivations for their actions (Ayal & Gino, 2012; Bénabou & Tirole, 2006; Mazar et al, 2008). However, in an intergroup context, people tend to act as interchangeable members of their group, and their actions are more likely driven by the social representation than by the personal self; in these situations, people are often motivated to represent their group in the best light possible and to monitor threat to the social image of their group whether it is negatively or positively represented (Ashokkumar et al, 2019; Pacilli et al, 2022; Rullo et al, 2019). Hence, social comparison might help to extend personal moral concerns to group moral concerns, motivating people to maintain a moral posture.…”
Section: Discussionmentioning
confidence: 99%